1974
DOI: 10.1136/pgmj.50.579.53
|View full text |Cite
|
Sign up to set email alerts
|

Lipomatous pseudohypertrophy of the pancreas associated with chronic pulmonary suppuration in an adult

Abstract: Case reports 53 overall mortality, of the order of 10-25% in several collected series (Bigler, 1960; Marshall and Hartzog, 1964; Sarmiento, 1966). More frequent early surgical intervention with antibiotic cover might conceivably lead to a reduction in this figure. AcknowledgmentWe wish to thank Professor F. McKeown, Pathology Department, Queen's University of Belfast for her detailed pathological examination of the gall bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…2,4,6,7,9,10,1416,26,27 Hoyer 16 discussed the possibility of a congenital anomaly, in view of the incidence in childhood, but thought that the condition was more probably acquired, due to injury of the pancreatic parenchyma by infective or toxic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6,7,9,10,1416,26,27 Hoyer 16 discussed the possibility of a congenital anomaly, in view of the incidence in childhood, but thought that the condition was more probably acquired, due to injury of the pancreatic parenchyma by infective or toxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…4,40 Yoshimura et al 10 and Sasaki et al 2 also reported that LPH might be related to chronic hepatitis B or other chronic advanced hepatic lesions that cause a fatty change and Mallory body formation. In fact, one of our patients had a fatty change in the right lobe of the liver, which was demonstrated by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search of Japana Centra Revuo Medicina and PubMed revealed only 27 other cases worldwide, including those in which the condition was diagnosed with imaging alone [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. Unlike steatosis resulting from obstruction of the pancreatic duct by pancreatolithiasis or a tumor, the causal factors of this disease are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic lipomatosis is also known as ''lipomatous pseudohypertrophy'' [4]. Lipomatous pseudohypertrophy is characterized macroscopically by enlargement of the pancreatic tissue and microscopically by replacement of the exocrine system by fat cells [5,6]. Besides, this situation is more common with conditions like obesity and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%